PENYISIHAN WARNA DAN BIODEGRADASI ORGANIK LIMBAH PEWARNAAN BATIK MENGGUNAKAN REAKTOR KONTINYU FIXED-BED ANAEROB-AEROB - Setyaningsih, Pudji
Abstract: Batik is well known as one of the most high valuable national cultures of Indonesia which maintenance, protection, enhancement and further development are considered necessary (Murtihadi & Mukminatun, 1979). The manufacture of batik contributes some negative impacts in addition to its advantages with some results of wastewater consist of colour, suspended solid, BOD, COD, phenol, total chrome, oil and grease, and pH that requires certain treatment and processing before thrown and washed away into the stream (Suleman, 1993). Dyeing process of batik usually takes naptha and indigosol as basic colour substances. Naptha is known as substance with two double bonds of nitrogen (-N=N-). Colour removal from azo chromophore can be obtained with the reduction from azo bond (-N=N-) (Michelsen et al.,1993). In anaerobic condition, the azo bond is reduced and partially divided into amine aromatic, which found some difficulties if to be degraded anaerobically, however, it is possibly executed aerobically (Wuhrman et al., 1980; Brown and Laboreur, 1983). Some aromatic amine are proved toxic and carsinogenic (Chung et al., 1978). Therefore anaerobic degradation may not be the last process of azo dye (Ganesh et al., 1994). The complete treatment consists of anaerobic and aerobic process is the appropriate measure of degrading azo dye (Brown et al., 1983). This research was aimed to detect the influence of detention time variations, waste concentration variations and variation of glucose as co-substrate in colour removal and organic reduction as COD (mg/L) from batik dye waste by means of anaerobic-aerobic fixed-bed continuous reactor, using mixed culture bacteria, anaerobic facultative which has been acclimatisized with the dye waste. A pre-treatment experiment under batch method has revealed some facts that dye waste is found stable in a condition of neutral pH for a period of 4-5 days and biodegradable as well. The anaerobic treatment becomes the first stages of the whole process. Waste dilution is conducted in several variations of 1:5, 1:4 and 1:3. The result indicates optimum for 1:5 with the colour removal percentage of 69,3%, while the COD reduction percentage is 56,6%. Within the glucose variation of 1000, 750 and 500 mg/L the optimum point is gained at the glucose concentration of 500 mg/L with the colour removal percentage of 44%, while the COD reduction percentage is 79,2%. The acclimatisation of continuous reactor is conducted in operational condition with detention time (td) of 27 hours, dilution (n) 1:5, and glucose concentration (Cg) of 1000 mg/L. From the detention time variations of 27, 30 and 33 hours, the optimum result is achieved at detention time of 27 hours with colour removal of 24%; 16,87%; 23,1%; 23,65%; 15,84% dan 15,76%; for absorbance value in wavelength of 372, 436, 525, 541, 603, and 620 nm. The COD reduction percentage for anaerobic is 24,9%; 48,9% for aerobic with the total reduction value of 61,7%. Waste concentration variation are 1:5, 1:4 and 1:3, which optimum condition is in dilution of 1:5, colour removal of 22,52%; 12,94%; 18,69%; 10,47%; 5,3 % and 0% for wavelength of 372, 436, 525, 541 603 and 620 nm. Percentage of COD reduction is 24,65% for anaerobic; 49,55% for aerobic and total value 61,94%. Within the glucose conentration variations of 1000, 75 and 500 mg/L, the optimum state is reached at the Cg of 500 mg/L, with colour removal percentage of 17,54%; 29,75%, 32,3%; 33,17%; 32,86% dan 31,56% for absorbance value in wavelength 372. 436, 525, 541, 603 and 620 nm. COD reduction percentage for anaerobic is 26,75%; 43,60% for aerobic; 58,60% for total value and COD metabolic 45,37%. The colour acceleration are 0,148; 0,085; 0,061; 0,058; 0,046 and 0,04 m\"\'/hour for each wavelength. The acceleration of COD removal in anaerobic condition is 3,417 mg/L/hour; 4,058 mg/L/hour for aerobic; 7,475 mg/L/hour for total and 4,35 mg/L/hour for metabolic. In optimum condition the observasion result of acetat acid is 55,23 ppm. From the gas observation, the highest volume of N2 is 90,84% v/v and 0,103 % v/v for methane (CH4). The bacteria identification in aerobic reactor has come up with 4 dominant species which are Pseudomonas alcaligenes, Providentia sp, Bacillus circulans and Klebsiella planticola. Effluent of primary colour (yellow, red and blue) and COD concentration (mg/L) match the prevailing quality standard.